Education in the Era of Digitization: An 'ABCDE' Model - Acharya, Yadav (Education and Development, 2022)
This study aims to explore the answers to the questions of how and what technology is bringing about radical changes in human life and how and what education system can make humans able to cope with the challenges posed by technology. To get the answer to these questions, I have followed the desk review strategy as a methodology. I essentially reviewed some related literature, heavily relying on internet-based literature. A systematic review process was followed to gather the relevant data from the text. The review was carried out in three steps: locating data sources to be used, defining criteria for rating the quality of the studies, and presenting and analyzing the findings.As the information was secondary as well as theoretical; themes were developed and then analyzed and interpreted accordingly. Exponential development of technology is bringing about unprecedented changes in various aspects of society. Now we are facing a radically changing situation in the job market. It is estimated that up to half of the world’s jobs are at high the risk of disappearing due to automation in the near future. It is the first time in human history that we have the possibility to follow everybody all the time and get to know someone better than one knows oneself. Inequality among human beings is mounting rapidly. Human abilities are gradually downgrading due to technological advancement. The study proposes an ‘ABCDE’ model of education to make children able to cope with the changing situation.